Distribution and current status of natural enemies of Paropsis charybdis in New Zealand - Murray, T.J.; Withers, T.M.; Mansfield, S.; Bain, J. (New Zealand Plant Protection, 2008)
In the 1970s and 1980s two natural enemies of the eucalyptus tortoise beetle Paropsis charybdis an invasive pest from Australia were established in New Zealand Cleobora mellyi (Coccinellidae) remained localised to the Marlborough Sounds but Enoggera nassaui (Pteromalidae) showed a significant impact and spread throughout the country A selfintroduced hyperparasitoid Baeoanusia albifunicle (Encyrtidae) has recently disrupted the biological control of P charybdis by E nassaui Another selfintroduced parasitoid Neopolycystus insectifurax (Pteromalidae) has also appeared As the distributions of the three parasitoids and C mellyi throughout the eucalypt growing areas of New Zealand were largely unknown historical records were reviewed and a field survey of selected areas was carried out The three parasitoids are widely distributed and despite some recent inundative releases of C mellyi it does not appear to have established in other geographical areas yet The effectiveness of the biocontrol agents against P charybdis will be the focus of future research